Optimizing Community and SME’s Potential in Sangketan Village, Tabanan, Bali: A Tax Compliance Perspective - ANDRIATI, Ni Putu Iin; PRABANINGRUM, Putu Ary Sandria; SUDIRGA, I Gusti Ayu Desni Saraswati; NOVIARI, Naniek; JATI, I Ketut; SISDYANI, Eka Ardhani; KRESNANDRA, Anak Agung Ngurah Agung (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2023)
Sangketan Village, located in Penebel District, Tabanan Regency, Bali, has excellent potential to improve and explore. The geographical situation of the village, which has an area of 12.70 km2 with a population of 3,515 people divided into 1,257 Family Cards and the livelihood of the majority of the population as coffee farmers encourages optimization of the management of coffee and other products so that they are better known and recognized in the broader range such as product export. Therefore, as a form of community service, the Diploma III Taxation Study Program, Diploma III Accounting Study Program, and Accounting Study Program, Faculty of Economics and Business, Udayana University provides outreach related to tax compliance for SME players to increase their productivity in terms of product use by foreign investment operating in Indonesia, such as hotels and villas. The socialization method begins with looking for phenomena faced by SMEs in Bali, which is then continued with field studies so that the right topic can be socialized. The results achieved from this service are increasing public awareness regarding compliance in carrying out tax obligations and increasing productivity and recognition of local products from Sangketan Village in a broader range.